ANALISIS KOMUNITAS ONLINE: PRODUKTIVITAS FEMALE DAILY SEBAGAI RUANG MEMPEROLEH DAN MEREKOMENDASIKAN PRODUK - retnandita, asa nadia (Jurnal Dinamika Sosial Budaya, 2022)
The online community is one of the interesting things to research. History, activities, participation among members, stakeholders, habits, and problems in online communities are important things to explore. As in this study, which focuses on analyzing the online community of Female Daily, which is a forum and space for its members to interact with each other through sharing experiences, sharing reviews, and accessing information about beauty products. The purpose of this study is to find out more about the relationship between history, activities, participation among members, habits, and problems that exist in the Female Daily Online Community. This research uses PAR method (Participatory Action Research) or participatory research method. In this study, the data sources used are primary and secondary data from news about Female Daily, websites, applications and room talk owned by Female Daily. The data will be analyzed by a descriptive analysis method.